1999
DOI: 10.1016/s0022-5223(99)70326-0
|View full text |Cite
|
Sign up to set email alerts
|

Potential mechanism of left ventricular outflow tract obstruction after mitral ring annuloplasty

Abstract: The semirigid Physio ring was associated with perturbations in annular dynamics that caused changes in papillary muscle geometry. We propose an integrated valvular-subvalvular mechanism to explain displacement of the anterior leaflet into the left ventricular outflow tract after mitral ring annuloplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 13 publications
0
13
0
2
Order By: Relevance
“…1 In support of this theory, Dagum et al demonstrated that a semirigid (C-E Physio) complete ring markedly displaced the lateral annulus (by 6.9Ϯ3.5 mm) toward the septum at endisovolumic contraction (before ejection began), and the anterolateral papillary muscle moved septally by 3.1Ϯ1.6 mm; conversely, a complete flexible (Medtronic Duran) ring displaced the lateral annulus by 4.1Ϯ4.7 mm toward the septum at end-isovolumic contraction without dislocating either papillary muscle. 26 Applying that same reference system (origin based on the highest septal marker) to the present dataset revealed that pulling the Paneth annuloplasty sutures moved the lateral annulus closer to the septum by only 3Ϯ1 mm without moving the papillary muscles, and the posterior leaflet remained mobile.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…1 In support of this theory, Dagum et al demonstrated that a semirigid (C-E Physio) complete ring markedly displaced the lateral annulus (by 6.9Ϯ3.5 mm) toward the septum at endisovolumic contraction (before ejection began), and the anterolateral papillary muscle moved septally by 3.1Ϯ1.6 mm; conversely, a complete flexible (Medtronic Duran) ring displaced the lateral annulus by 4.1Ϯ4.7 mm toward the septum at end-isovolumic contraction without dislocating either papillary muscle. 26 Applying that same reference system (origin based on the highest septal marker) to the present dataset revealed that pulling the Paneth annuloplasty sutures moved the lateral annulus closer to the septum by only 3Ϯ1 mm without moving the papillary muscles, and the posterior leaflet remained mobile.…”
Section: Discussionmentioning
confidence: 70%
“…24 Complete rings may predispose toward LV outflow tract obstruction by flattening the annulus 23 and reducing annular flexion. 25,26 Paneth suture tightening did not reduce annular shortening or flexion compared with the ischemic state, thus preserving the putative advantages of normal annular dynamic motion. Notably, although partial flexible rings abolish septal-lateral and commissure-commissure shortening 4 and freeze the posterior leaflet 16 , they also preserve annular flexion.…”
Section: Discussionmentioning
confidence: 90%
“…In addition to this dynamic, we confirmed the folding annular dynamics after MEMO implantation, which was expressed as the increase rate in the AHCWR from the end-diastole to the end-systole period. The folding dynamics may also be important for long-term valve function and prevention of left ventricular outflow tract obstruction after annular ring implantation [15]. Dagum and colleagues [4] proved this dynamic after flexible annular ring implantation in an animal model.…”
Section: Commentmentioning
confidence: 99%
“…A troca mitral com preservação da continuidade músculo papilar-anel valvar é de suma importância na manutenção da geometria ventricular (25)(26)(27)(28)(29)(30) . Num trabalho recente, foram comparadas plastia mitral, troca mitral com manutenção da continuidade músculo papilar-anel valvar, e troca sem manutenção da continuidade músculo papilaranel valvar (31) .…”
Section: Comentáriosunclassified
“…Pode também ser utilizado mesmo que a relação diâmetro longitudinal e transversal de 3:4 não esteja mantida, o que ocorre em cerca de 10% dos casos e que contraindica o anel semi-rígido (41,42) . Foi demonstrado que o anel maleável não distorce o segmento aórtico do anel mitral como o rígido, o que interferiria com a distribuição da tensão por todo o folheto anterior (30,43) . Ainda, o anel maleável interfere menos com o ângulo mitro-aórtico (44) , na geometria ventricular e disposição dos mús-culos papilares, tendo menor chance de causar SAM e obstrução do trato de saída do ventrículo esquerdo (30) .…”
Section: Comentáriosunclassified